Динаміка життєстійкості осіб із різним рівнем антиципаційної спроможності в період кризових подій у країні - Штриголь, Д. В.; Горбик, Н. К.; Shtrygol, D. V.; Horbyk, N. K.; ORCID: http://orcid.org/0000-0001-7346-2677 (Право і безпека. - 2015. - № 2 (57). - С. 232–237., 2015)
Досліджено взаємозв’язок антиципаційної спроможності та життєстійкості. Розглянуто зміни життєстійкості за річний період спостереження під час початку кризових подій у країні. Встановлено, що в осіб з антиципаційною спроможністю в період кризи спостерігається підвищення рівня життєстійкості. В осіб з антиципаційною неспроможністю спостерігається зниження рівня життєстійкості, що можна розцінювати як віддзеркалення несприятливого процесу пристосування до критичної ситуації. Отримані результати можна використовувати при диференційованому проведенні профілактичної, психокорекційної роботи та кризисного консультування з урахуванням антиципаційної спроможності клієнтів.

For successful socialization and opposition to stress factors it is necessary anticipation ability, which is the ability of a human to imagine the possible result of the action before its realization. Studying forecasting in the system of properties of a healthy personality is a perspective area of research that will make possible for better understanding the functions of anticipation ability, its interconnections with other individual and psychological characteristics, the possibility to develop forecasting abilities. The changes of students’ vitality with different level of anticipation for the annual period of observation during the beginning of crisis events in the country are analyzed in the article. The author of the research has found out that before the crisis events in Ukraine there were no significant differences in the level of students’ vitality with different level of anticipation. Next the level of involvement in life, awareness of the possibility to influence on occurring events, the ability to take risks has increased within studied people with anticipation ability. This is a certain way of coping with stress and the ability to predict future events that may occur. Dynamics of vitality of people with anticipation failure show a decline of vitality level. Feelings that the activity is not fun, own helplessness, inability to influence the unexpected situations became characteristic for them. But reduction of risk-taking is changed by the increased confidence that everything that happens to us, gives some experience and knowledge. Such a «fluctuation» is a sort of resource for the studied people with anticipation failure to «combat» the events in the country. Results of the study can be viewed as a reflection of the adverse process of adaptation to the critical situation of people with anticipation failure.

Исследована взаимосвязь антиципационной состоятельности и жизнестойкости. Рассмотрены изменения жизнестойкости за годичный период наблюдения во время начала кризисных событий в стране. Установлено, что у лиц с антиципационной состоятельностью в период кризиса наблюдается повышение уровня жизнестойкости. У лиц с антиципационной несостоятельностью наблюдается снижение уровня жизнестойкости, что можно расценивать как отражение неблагоприятного процесса приспособления к критической ситуации. Полученные результаты могут быть использованы при дифференцированном проведении профилактической, психокоррекционной работы и кризисного консультирования с учётом антиципационной состоятельности клиентов.
Shtrygol, D.V. and Horbyk, N.K. (2015), “Dynamics of vitality of people with different level of anticipation ability during crisis events in the country” [“Dynamika zhyttiestiikosti osib iz riznym rivnem antytsypatsiinoi spromozhnosti v period kryzovykh podii u kraini”], Pravo i Bezpeka, No. 2, pp. 232–237.
Штриголь, Д. В. Динаміка життєстійкості осіб із різним рівнем антиципаційної спроможності в період кризових подій у країні / Д. В. Штриголь, Н. К. Горбик // Право і безпека. - 2015. - № 2 (57). - С. 232–237.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; антиципація; життєстійкість; криза; кризисне консультування; профілактика; cтрес; anticipation; vitality; crisis; crisis intervention; prevention; stress; антиципация; жизнестойкость; кризис; кризисное консультирование; профилактика; cтресс